2015
DOI: 10.1371/journal.pone.0139763
|View full text |Cite|
|
Sign up to set email alerts
|

Modular Coils with Low Hydrogen Content Especially for MRI of Dry Solids

Abstract: IntroductionRecent advances have enabled fast magnetic resonance imaging (MRI) of solid materials. This development has opened up new applications for MRI, but, at the same time, uncovered new challenges. Previously, MRI-invisible materials like the housing of MRI detection coils are now readily depicted and either cause artifacts or lead to a decreased image resolution. In this contribution, we present versatile, multi-nuclear single and dual-tune MRI coils that stand out by (1) a low hydrogen content for hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…22,23 First approaches towards practicable intraoral MR imaging using special teeth coils are available -hence, there is potential for in vivo application of UTE-MRI after coil and sequence optimization. [24][25][26][27][28] While air-tissue interface artifacts are avoided by using UTE-MRI, signal artifacts from surrounding water-rich tissue remain an issue and could be minimized by using spiral sequences or the pointwise encoding time reduction with radial acquisition (PETRA) sequence. 29,30 Other approaches described to this issue include the use of hydrogen-poor materials for the construction of coil, bed and support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 First approaches towards practicable intraoral MR imaging using special teeth coils are available -hence, there is potential for in vivo application of UTE-MRI after coil and sequence optimization. [24][25][26][27][28] While air-tissue interface artifacts are avoided by using UTE-MRI, signal artifacts from surrounding water-rich tissue remain an issue and could be minimized by using spiral sequences or the pointwise encoding time reduction with radial acquisition (PETRA) sequence. 29,30 Other approaches described to this issue include the use of hydrogen-poor materials for the construction of coil, bed and support.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Other approaches described to this issue include the use of hydrogen-poor materials for the construction of coil, bed and support. 24 In addition, other promising approaches are available to obtain additional information by MRI examination of dense biological materials about discriminating bound from pore water based on their relaxation properties. 31 The extent to which this possible approach for human bone can be transferred to human teeth should be clarified by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sequences have been developed to capture short-lived signals, including single-point imaging (2) and the particularly efficient techniques employing three-dimensional (3D) radial center-out encoding with ultrashort (3,4) or even zero echo time (TE) (5)(6)(7)(8)(9). However, on the downside of increased short-T2 sensitivity, with these sequences also signals from solid hardware parts are detected, particularly from the radiofrequency (RF) coils (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, ideally, the undesired signal is avoided in the first place at the level of coil design and construction. So far, this challenge has been approached with loop‐gap resonators where the self‐supporting conductor facilitates avoiding additional materials. However, such coils are often not suitable for human in vivo MRI due to their orientation with respect to the main field and missing electrical isolation of the conductor toward the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, however, MRI sequences with very short echo time (TE) were reported that enabled fast soft- and hard-tissue imaging of hydrogen and other nuclei like sodium 1 2 3 4 5 6 7 8 . This development stimulated a rising interest in dental MRI 9 10 11 12 13 14 15 , and detailed images with soft- and hard-tissue contrast of extracted human teeth were already obtained ex vivo: Using a small-bore MRI system at high field in conjunction with ultra-short-TE (UTE), zero-TE (ZTE), sweep imaging with Fourier transformation (SWIFT) or single-point imaging (SPI), a voxel size of the order of 100 μm 3 was achieved.…”
mentioning
confidence: 99%